The Average IFN-γ Secreting Capacity of Specific CD8+ T Cells Is Compromised While Increasing Copies of a Single T Cell Epitope Encoded by DNA Vaccine - Yanmin Wan; Jing Wang; Haizhu Zhou; Zhidong Hu; Xiaonan Ren; Jianqing Xu (Clinical and Developmental Immunology)
Previous studies suggested that both the frequency and the mean fluorescence intensity (MFI) of cytokine secreting T cells could be of great value for immunogenicity evaluation of a vaccine. In this study, by constructing epitope-based DNA vaccines encoding a previously identified CD8+ T cell epitope, we investigated the influence of multiplying epitope copies on both the frequency and the MFI of specific IFN-γ secreting CD8+ T cells. We found that frequencies of specific CD8+ T cell could be improved by multiplying epitope copies, while the MFI of IFN-γ secreted by epitope-specific CD8+ T cells decreased synchronously. And further analysis showed that the decrease of MFI was not caused by the functional avidity variation of CD8+ T cell receptor.